(untitled) (International Journal of Engineering and Computer Science, 2017)
Energy meter reading tedious process. Now a day energy meter reader goes to every premise and takes the reading manually then issues the bill. In manually reading human error possible and not provide reliable meter reading. To avoid this difficult task Automatic Energy Meter Reading (AMR) system is introduced. AMR is the technology that automatically collecting consumption and status of data from energy metering device and transferring the data to Electricity Board (EB) office by using Wireless Sensor Networks (WSN). After verifying customer‟s serial number bill will be issued then data has been stored into database. The proposed system automatically disconnect meter either load crosses concern limit or payment periods exists. It also does not provide electricity tampering and provide accurate meter reading.